2015
DOI: 10.1039/c4tc02409e
|View full text |Cite
|
Sign up to set email alerts
|

Multi-color luminescence of uniform CdWO4nanorods through Eu3+ion doping

Abstract: Uniform Eu 3+ doped CdWO 4 nanorods were prepared via a simple hydrothermal method and characterized by X-ray diffraction, transmission electron microscopy, photoluminescence (PL) spectroscopy and PL lifetime measurement. The results indicate that the obtained Eu 3+ doped CdWO 4 nanorods have monoclinic phase structure, and the phase structure can be retained at Eu 3+ doping concentrations of 0.4%~4.0%. The diameter of nanorods decreases from 27 to 15 nm with an increase in the doping concentrations, and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 62 publications
3
25
0
Order By: Relevance
“…The excitation spectrum monitored at 614 nm shows an asymmetrical broad‐band at the range of 230–330 nm, which is corresponding to the O 2− →Eu 3+ and O 2− →W 6+ charge transfer state transitions [23, 25, 31]. Additionally, the sharp line peaked at 394 nm is assigned to the 7 F 0 – 5 L 6 transitions of Eu 3+ ions [22, 32]. Meanwhile, it is also worth noting that the ZnWO 4 :Eu 3+ phosphors exhibit a broad‐band emission centred at 489 nm, called ‘intrinsic luminescence’ and which is caused by the electron transition between the O 2p orbitals and the empty d orbitals of the central W 6+ ions in WO 4 2− groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The excitation spectrum monitored at 614 nm shows an asymmetrical broad‐band at the range of 230–330 nm, which is corresponding to the O 2− →Eu 3+ and O 2− →W 6+ charge transfer state transitions [23, 25, 31]. Additionally, the sharp line peaked at 394 nm is assigned to the 7 F 0 – 5 L 6 transitions of Eu 3+ ions [22, 32]. Meanwhile, it is also worth noting that the ZnWO 4 :Eu 3+ phosphors exhibit a broad‐band emission centred at 489 nm, called ‘intrinsic luminescence’ and which is caused by the electron transition between the O 2p orbitals and the empty d orbitals of the central W 6+ ions in WO 4 2− groups.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, using a single-phase white-light-emitting phosphor instead of phosphor blends could help to reduce some of this variability [16][17][18][19]. Under deep ultraviolet excitation, zinc tungstate (ZnWO 4 ) can exhibit a broad, intrinsic blue-green emission due to a charge transfer between oxygen and tungsten ions in the WO 4 2− groups [20][21][22][23]. When doped with Eu 3+ ions, ZnWO 4 not only emits blue-green light but also effectively transfers energy to Eu 3+ ion, generating red emissions, which becomes a potential white-light-emitting phosphor [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The contained high‐ Z elements tungsten and gadolinium endow GWOT@MC540 NPs with the potential to be dual‐modal contrast agents for both CT and MRI . As shown in Figure a,b, GWOT@MC540 NPs exhibited a stronger CT imaging ability than iohexol, with a slope of 21.1 HU mL mg −1 (GWOT@MC540) vs. 16.2 HU mL mg −1 (iohexol) .…”
Section: Methodsmentioning
confidence: 97%
“…This activates MC540 and initiates X‐PDT, while the contained high‐ Z elements can spontaneously interact with X‐rays as radiosensitizers to enhance the RT efficiency, thus achieving synergistic RT&X‐PDT. Meanwhile, the GWO matrix is endowed with a dual‐modal imaging capacity, as Gd 3+ ‐based contrast agents for MRI have been shown to greatly improve the accuracy of diagnosis due to their high r 1 value, while it has already been demonstrated that W‐based contrast agents have great potential for CT . To the best of our knowledge, there is no report on GWO‐based nanoscintillators that have been designed as multifunctional nanoagents for cancer theranostics.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that in solid-state luminescent materials where possibility of energy transfer process exists, when the host materials or sensitizers are excited (indirect excitation), some luminescence decay curves from the rare-earth activator could follow a non-exponential function [46,47]. As discussed that for Ag 2 MoO 4 :Eu 3+ phosphor, there exists significant amount of energy transfer from MoO 4 2− anionic complex to Eu 3+ excitation at 260 nm, and this is followed by the luminescence decay from the 5 D 0 level of Eu 3+ .…”
Section: Moo 4 2− To the Eu 3+ Energy Transfermentioning
confidence: 99%